Developing Interactive Learning Media of “Venn Gram” to Improve Conceptual Understanding of Set Operations - Fadhanila Syainuralita Prillyana; Hendarto Cahyono; Anis Farida Jamil (Department of Mathematics Education University of Muhammadiyah Malang, 2020)
This research aimed at discovering the validity and effectiveness of the interactive media of